Shifts in estuarine zooplankton variability following extreme climate events: a comparison between drought and regular years - Marques, Sónia Coutrim (2015)
Climate change will likely lead to an increase in temperature and an occurrence of extreme droughts and floods in the 21st century. In particular, coastal and estuarine systems are highly sensitive to climate extremes and changing precipitation patterns, and thus offer invaluable scenarios for the evaluation of climate variability. Zooplankton assemblages and hydroclimate variables were monitored for 8 yr. The main objective was to assess the impact of climate variability, particularly of the 2 most recent drought events in the Mondego estuary (Portugal, southern Europe), which occurred in 2004−2005 and 2007−2008, on the zooplankton population dynamics, with emphasis on how stochastic extrinsic perturbation might influence these populations. Principal component analysis revealed dramatic environmental changes during drought periods, which were reflected in the seasonal and inter-annual patterns in the zooplankton, indicating that hydroclimate forcing is critical in defining zooplankton dynamics. Lower precipitation and higher salinities were the main drivers for the observed patterns, i.e. a major penetration of seawater led to a higher prevalence of marine species. Results also revealed a conspicuous increase in warm water taxa since 2006, which was significantly related to pronounced changes in water temperature. This synchronous variability between water temperature and zooplankton abundance, which had not been evaluated and discriminated in previous studies, suggests the potential impact of warming on zooplankton assemblages. Hence, this study demonstrates the crucial role of zooplankton as valuable indicators of hydrological changes associated with climate factors in estuarine ecosystems.